Fractal-Based Thinned Planar-Array Design Utilizing Iterative FFT Technique - Wentao Li; Yongqiang Hei; Jing Yang; Xiaowei Shi (International Journal of Antennas and Propagation, 2012)
This paper investigated the synthesis problem of fractal-based thinned planar arrays by using the iterative Fourier technique (IFT). Since an inverse discrete Fourier transform relationship exists between the array factor and the element excitations for a periodic array antenna, an iterative Fourier technique is introduced to derive the array element excitation from the prescribed array factor based on this peculiar property. However, considering the IFT technique is sensitive to the initial values, the fractal-thinned array technique is employed and combined in the synthesis process to exploit the advantages of these two techniques. Moreover, the DRR of the excitation amplitude is controlled to achieve a reduction of the cost of the feeding network. Numerical examples have been carried out to validate the proposed approach.